Evaluation of Three Influenza A and B Real-Time Reverse Transcription-PCR Assays and a New 2009 H1N1 Assay for Detection of Influenza Viruses - Selvaraju, Suresh B; Selvarangan, Rangaraj (Journal of Clinical Microbiology, 2010)
The performance characteristics of three real-time influenza A/B virus reverse transcription-PCR (RT-PCR) assays and two real-time 2009 H1N1 RT-PCR assays were evaluated using previously characterized clinical specimens. A total of 150 respiratory specimens from children (30 influenza A/H1 virus-, 30 influenza A/H3 virus-, 30 2009 H1N1-, and 30 influenza B virus-positive specimens and 30 influenza virus-negative specimens) were tested with the CDC influenza A/B PCR (CDC), ProFlu⁺ multiplex real-time RT-PCR assay (ProFlu⁺), and MGB Alert Influenza A/B & RSV RUO (MGB) assays. A second set of 157 respiratory specimens (100 2009 H1N1-, 22 seasonal influenza A/H1-, and 15 seasonal influenza A/H3-positive specimens and 20 influenza-negative specimens) were tested with a new laboratory-developed 2009 H1N1 RT-PCR and the CDC 2009 H1N1 assay. The overall sensitivities of the CDC, ProFlu⁺, and MGB assays for detection of influenza A and B viruses were 100%, 98.3%, and 94%, respectively. The ProFlu⁺ assay failed to detect one influenza A/H1 virus-positive specimen and yielded one unresolved result with another influenza A/H1 virus-positive specimen. The MGB assay detected 84/87 (96.5%) of influenza A and B viruses and 26/30 (86.6%) of 2009 H1N1 viruses. The new laboratory-developed 2009 H1N1 RT-PCR assay detected 100/100 (100%) 2009 H1N1 virus-positive specimens, while the CDC SW Inf A and SW H1 PCR assays failed to detect one and three low-positive 2009 H1N1-positive specimens, respectively. The CDC influenza A/B virus assay and the newly developed 2009 H1N1 RT-PCR assay with an internal control can be set up in two separate reactions in the same assay for routine clinical testing to detect influenza A and B viruses and to specifically identify the 2009 H1N1 influenza virus.